Solving One-Predator Two-Prey System by using Adomian Decomposition Method / Wan Khairiyah Hulaini Wan Ramli... [et. al] - Wan Khairiyah Hulaini, Wan Ramli; Muhammad Saufi Firdaus, Azmi; Farahanie, Fauzi; Norlaila, Md Nor (Unit Penerbitan UiTM Kelantan, 2016)
In this paper, a mathematical model of one-predator two-prey system is discussed. This model is derived from predator-prey Lotka-Volterra model by adding another population of prey into the system. The model derived is a nonlinear system of ODEs. So the approach to this model is different from the linear system of ODEs. With reference to that, Adomian Decomposition Method (ADM) is one of the semi-analytical approaches being applied in this paper to solve the system. The approximate solution is made until four terms. The solution obtained is analyzed graphically.